Aspartate Transaminase AST2 Involved in Sporulation and Necrotrophic Pathogenesis in the Hemibiotrophs Magnaporthe oryzae and Colletotrichum graminicola - Zhang, Penghui; Fang, Zhenyu; Song, Yanyue; Wang, Shaowei; Bao, Lina; Liu, Mingyu; Dang, Yuejia; Wei, Yi; Zhang, Shi-Hong (Frontiers in Microbiology, 2022)
Aspartate family includes five additional amino acids other than aspartate, among which most except aspartate have been reported for their action in pathogenesis by amino acid biosynthesis. However, how aspartate, the initial substrate of this family metabolic pathway, is involved in pathogenesis remains unknown. Here, we focused on aspartate transaminase (AST) that catalyzes transamination reaction between glutamate-aspartate in Magnaporthe oryzae. Three MoAST genes were bioinformatically analyzed, of which MoAST2 was uniquely upregulated when invasive hyphae switched to necrotrophic pathogenesis. MoAST2 deletion (ΔMoast2) caused a drastic reduction in conidiogenesis and appressorium formation. Particularly, ΔMoast2 was observed to be proliferated at the biotrophic phase but inhibited at the necrotrophic stage, and with invisible symptoms detected, suggesting a critical role in necrotrophic phase. Glutamate family restored the ΔMoast2 defects but aspartate family did not, inferring that transamination occurs from aspartate to glutamine. MoAST2 is cytosolic and possessed H2O2 stress tolerance. In parallel, Colletotrichum graminicola AST2, CgAST2 was proven to be a player in necrotrophic anthracnose development. Therefore, conserved AST2 is qualified to be a drug target for disease control.